Low energy availability as a key factor in exercise-induced menstrual dysfunction – a narrative review - Szulim, Julia; Petelicki, Kacper; Biełanowicz, Ewa; Agnieszka Tora,; Barszcz, Aleksandra; Pondo, Wojciech (Quality in Sport, 2026)
Background. Low energy availability (LEA) is increasingly recognized as a key factor underlying physiological disturbances in physically active women, particularly exercise-induced menstrual dysfunction (EIMD). Energy imbalance may impair reproductive function via neuroendocrine disruption of the hypothalamic–pituitary–gonadal axis. Aim. This narrative review synthesizes current evidence on LEA as an etiological factor in EIMD, focusing on physiological mechanisms, spectrum of menstrual disorders, and clinical implications within the Female Athlete Triad and Relative Energy Deficiency in Sport (RED-S) frameworks. Material and methods. A targeted literature search was conducted in PubMed and supplemented by Google Scholar. Over twenty key publications were selected based on relevance and scientific quality, including consensus statements, reviews, and original experimental and observational studies. Results. LEA was identified as the primary driver of EIMD, acting through suppression of gonadotropin-releasing hormone pulsatility and reduced luteinizing hormone secretion. These changes lead to menstrual disturbances ranging from luteal phase defects and anovulation to oligomenorrhea and functional hypothalamic amenorrhea. Evidence suggests that energy deficiency, rather than exercise itself, is the main causal factor. LEA also underlies broader syndromes such as the Female Athlete Triad and RED-S, affecting multiple physiological systems beyond reproduction. Conclusions. LEA is a key modifiable factor in prevention and management of EIMD. Early identification and restoration of adequate energy availability are essential to prevent short- and long-term health consequences in physically active women.